Role of modern technologies for sustainable genetic improvement of African livestock - Ibeagha-Awemu, E.M.; Peters, S.O.; Bemji, M.N.; Feugang, J.M.; Osei-Amponsah, R.; Trocmé, D.; Mrode, Raphael A. (Springer, 2025)
Evidence of the impact of advanced technologies in genetics, nutrition and health management in the last seven decades has led to a twofold increase in the milk produced by a Holstein cow and a fourfold increase in the size of a broiler chicken in Western countries. Therefore, harnessing breakthrough technologies of genomic breeding, reproduction, management practices (health and environment), etc., with supporting infrastructure, funding and technical know-how is key to solving current problems and achieving rapid developments in the African livestock sector. This chapter presents an overview of some modern technologies that have played and continue to play significant roles in advancing sustainable genetic improvement in the livestock sector. Firstly, Section 20.2 presents the key issues impeding sustainable livestock improvement within Africa’s complex livestock production systems. Then the phenomics technologies used for data capture to support genetic selection are presented in Section 20.3 followed by the breakthrough genomics technologies responsible for sustained genetic improvements in livestock traits (Section 20.4). The emerging technologies of genome editing (Section 20.4.3) and cellular agriculture (Section 20.4.4) are also presented. Breakthrough reproductive technologies that have been responsible for the spread of high-merit genetics are examined in Section 20.5. This chapter concludes with future perspectives (Section 20.6) on how the adoption and implementation of modern genomic technologies can accelerate desired improvements in the African livestock sector.